K2-139 b: a low-mass warm Jupiter on a 29-d orbit transiting an active K0 V star. Issue 2 (13th December 2017) - Barragán, O; Gandolfi, D; Smith, A M S; Deeg, H J; Fridlund, M C V; Persson, C M; Donati, P; Endl, M; Csizmadia, Sz; Grziwa, S; Nespral, D; Hatzes, A P; et al.
Abstract: We announce the discovery of K2-139 b (EPIC 218916923 b), a transiting warm-Jupiter ( T eq = 547 ± 25 K) on a 29-d orbit around an active (log $R^′ _HK$ = −4.46 ± 0.06) K0 V star in K2 Campaign 7. We derive the system's parameters by combining the K2 photometry with ground-based follow-up observations. With a mass of $0.387 _{ - 0.075 } ^ {+ 0.083 }$ M J and radius of $0.808 _{ - 0.033 } ^ {+ 0.034 }$ R J, K2-139 b is one of the transiting warm Jupiters with the lowest mass known to date. The planetary mean density of $0.91 _{ - 0.20} ^ { + 0.24 }$ g cm −3 can be explained with a core of ∼50 M⊕ . Given the brightness of the host star ( V = 11.653 mag), the relatively short transit duration (∼5 h), and the expected amplitude of the Rossiter–McLaughlin effect (∼25m s −1 ), K2-139 is an ideal target to measure the spin-orbit angle of a planetary system hosting a warm Jupiter.